Intraaortic Balloon Pump in Cardiogenic Shock Complicating Acute Myocardial Infarction: Long-Term 6-Year Outcome of the Randomized IABP-SHOCK II Trial - Thiele, Holger; Zeymer, Uwe; Thelemann, Nathalie; Neumann, Franz-Josef; Hausleiter, Jörg; Abdel-Wahab, Mohamed; Meyer-Saraei, Roza; Fuernau, Georg; Eitel, Ingo; Hambrecht, Rainer; Böhm, Michael; Werdan, Karl; et al. (Circulation (New York, N.Y.), 2019)
The role of intraaortic balloon counterpulsation (IABP) in cardiogenic shock is still a subject of intense debate despite the neutral results of the IABP-SHOCK II trial (Intraaortic Balloon Pump in Cardiogenic Shock II) with subsequent downgrading in international guidelines. So far, randomized data on the impact of IABP on long-term clinical outcomes in patients with cardiogenic shock complicating acute myocardial infarction are lacking. Furthermore, only limited evidence is available on general long-term outcomes of patients with cardiogenic shock treated by contemporary practice. The IABP-SHOCK II trial is a multicenter, randomized, open-label trial. Between 2009 and 2012, 600 patients with cardiogenic shock complicating acute myocardial infarction undergoing early revascularization were randomized to IABP versus control. Long-term follow-up was performed 6.2 years (interquartile range 5.6-6.7) after initial randomization. Follow-up was completed for 591 of 600 patients (98.5%). Mortality was not different between the IABP and the control group (66.3% versus 67.0%; relative risk, 0.99; 95% CI, 0.88-1.11; =0.98). There were also no differences in recurrent myocardial infarction, stroke, repeat revascularization, or rehospitalization for cardiac reasons (all >0.05). Survivors' quality of life as assessed by the EuroQol 5D questionnaire and the New York Heart Association class did not differ between groups. IABP has no effect on all-cause mortality at 6-year long-term follow-up. Mortality is still very high, with two thirds of patients with cardiogenic shock dying despite contemporary treatment with revascularization therapy. URL: https://www. gov/. Unique identifier: NCT00491036.